If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 7) = 10x + -7 Reorder the terms: 3(7 + 4x) = 10x + -7 (7 * 3 + 4x * 3) = 10x + -7 (21 + 12x) = 10x + -7 Reorder the terms: 21 + 12x = -7 + 10x Solving 21 + 12x = -7 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 21 + 12x + -10x = -7 + 10x + -10x Combine like terms: 12x + -10x = 2x 21 + 2x = -7 + 10x + -10x Combine like terms: 10x + -10x = 0 21 + 2x = -7 + 0 21 + 2x = -7 Add '-21' to each side of the equation. 21 + -21 + 2x = -7 + -21 Combine like terms: 21 + -21 = 0 0 + 2x = -7 + -21 2x = -7 + -21 Combine like terms: -7 + -21 = -28 2x = -28 Divide each side by '2'. x = -14 Simplifying x = -14
| -7q-(-7-2q)=-3 | | 6x+x=98 | | 7n+6-6n=-1 | | w^25=w | | n+n+1+n+2=-24 | | 6=8k-(10k+3) | | 3(3n+2)=9(4n+5)+8 | | 6x+y=98 | | -40-2b=-2+2(1-5b) | | 56=4x | | w^25= | | A(x-2)(x-3)= | | 2+m=-10 | | 6x+9=-108-7x | | -8q-3(q+4)=q+7 | | 6x+9=-1008-7x | | x-(-3)=-1 | | -4y-13=9y+13 | | -3+9x=3(x+6) | | 18b=-234 | | 2x+30=12x | | 3c+c=48 | | 4q+2(-8+3q)=3 | | 8x-73=3x-13 | | 3x-7=7x-9 | | -11n=99 | | 2-5v-6v=2 | | 2-5v-6v=23 | | 12-7x=144-35x | | 42=-3(4n-2) | | -p-8p=3-6p | | -32=-2v |